Financial Services, Economic Growth, and Well-Being: A Four-Pronged Study - Kashyap, Ravi (Indian Journal of Finance, 2015)
A four-pronged approach to dealing with social science phenomenon is outlined in the present paper. This methodology is applied to financial services, economic growth, and well - being. The four prongs are like the four directions for an army general looking for victory. Just like the four directions, we need to be aware that there is a degree of interconnectedness in the following four prongs. Uncertainty principle of the social sciences; Responsibilities of fiscal janitors; Need for smaller organizations; Redirecting growth that generates garbage. The importance of gaining a more profound comprehension of welfare and delineating its components into those that result from an increase in goods and services, and hence can be attributed to economic growth and into those that are not related to economic growth, but lead to a better quality of life were highlighted in the paper. The reasoning being that economic growth alone is an inadequate indicator of well-being. Hand in hand with a better understanding of the characteristics of welfare comes the need to consider the metrics we currently have that gauge economic growth and supplement those with measures that capture well-being more holistically.